Building resilient hospitals in the Eastern Mediterranean Region: lessons from the COVID-19 pandemic. (24th June 2022) - Khalil, Merette; Mataria, Awad; Ravaghi, Hamid
Abstract : Since the COVID-19 pandemic began, hospitals in the Eastern Mediterranean Region (EMR) have faced significant challenges in providing essential services, while simultaneously combatting this pandemic and responding to new and ongoing shocks and emergencies. Despite these challenges, policy-makers and hospital managers adapted their hospital responses to maintain operations and continue providing essential health services in resource-restraint and fragile and conflict affected, offering valuable insights to others in similar contexts. The aim of this paper is to share the lessons learnt from hospital responses to COVID-19 from the EMR. To do this, we triangulated findings from literature review, open-ended online surveys and 46 in-depth key informant interviews from 18 EMR countries. Qualitative findings from semistructured key informant interviews along with the open-ended survey responses resulted in nine major themes for lessons learnt in the EMR. These themes include Preparedness, Leadership and Coordination, Communication, Human Resources, Supplies and Logistics, Surge Capacity and Essential Services, Clinical Management (including Rapid Identification, Diagnosis and Isolation), Infection Prevention and Control, and Information and Research. Each of the nine themes (domains) included 4–6 major subthemes offering key insights into the regional hospital response to health emergencies. Resilient hospitals are those that can provide holistic, adaptable, primary-care-based health systems to deliver high-quality, effective and people-centred health services and respond to future outbreaks. Both bottom-up and top-down approaches are needed to strengthen collaboration between policy-makers, hospitals, front-line workers and communities to mitigate the continued spread of SARS CoV2, build resilient hospital systems and improve public health preparedness and emergency response.